Time‐ and spatial‐resolved XAFS spectroscopy in a single shot: new analytical possibilities for in situ material characterization. (14th April 2016) - Buzanich, Ana Guilherme; Radtke, Martin; Reinholz, Uwe; Riesemeier, Heinrich; Emmerling, Franziska
Abstract : A new methodology that offers both time‐resolved and simultaneous spatial‐resolved XAFS information was successfully implemented and tested at the BAMline at BESSY II. Abstract : A new concept that comprises both time‐ and lateral‐resolved X‐ray absorption fine‐structure information simultaneously in a single shot is presented. This uncomplicated set‐up was tested at the BAMline at BESSY‐II (Berlin, Germany). The primary broadband beam was generated by a double multilayer monochromator. The transmitted beam through the sample is diffracted by a convexly bent Si (111) crystal, producing a divergent beam. This, in turn, is collected by either an energy‐sensitive area detector, the so‐called color X‐ray camera, or by an area‐sensitive detector based on a CCD camera, in θ–2θ geometry. The first tests were performed with thin metal foils and some iron oxide mixtures. A time resolution of lower than 1 s together with a spatial resolution in one dimension of at least 50 µm is achieved.